1972
DOI: 10.1136/gut.13.4.270
|View full text |Cite
|
Sign up to set email alerts
|

A study of six patients with hypertrophy of the gastric mucosa with particular reference to albumin metabolism

Abstract: SUMMARY Six patients with hypertrophy of the gastric mucosa (Menetrier's disease) have been studied. An incorrect diagnosis was initially made in four patients. The correct diagnosis was suggested by the appearances either of barium meal radiographs of the stomach or at gastroscopy. Estimates of both basal and maximal gastric acid secretion were within normal limits. A definitive histological diagnosis requires an adequate full-thickness biopsy of the wall of the stomach; a peroral gastric mucosal biopsy is of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A lack of the trophic effect of gastrin has been suggested (Scott et al, 1975), but serum gastrin in patient 1 was high and was within the range that might be expected for patients with gastritis with antral sparing, which may occur in Menetrier's disease (Jones et al, 1972) and hypochlorhydria (Korman, Strickland and Hansky, 1971). The authors are not aware of other reports on gastrin levels in Menetrier's disease and consider that this finding merits further study.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…A lack of the trophic effect of gastrin has been suggested (Scott et al, 1975), but serum gastrin in patient 1 was high and was within the range that might be expected for patients with gastritis with antral sparing, which may occur in Menetrier's disease (Jones et al, 1972) and hypochlorhydria (Korman, Strickland and Hansky, 1971). The authors are not aware of other reports on gastrin levels in Menetrier's disease and consider that this finding merits further study.…”
Section: Discussionmentioning
confidence: 82%
“…The characteristic mucosal histology (Jones et al, 1972) was present in full-thickness sections of the operative specimens and in addition patient 1 was shown to have the hypochlorhydric mucus-rich gastric juice which is typical of the disease (Scott et al, 1975). In patient 3 only superficial biopsies were obtained which may be insufficient for a firm diagnosis (Jones et al, 1972) but the clinical and investigational findings make this diagnosis likely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this initial study predicted in larger groups of patients with Ménétrier's disease that hypoalbuminemia can be found in about 70% of patients and that in those cases in which this abnormality is investigated in metabolic studies with radioiodinated albumin, the low serum albumin can be shown to be due to an increased fractional albumin catabolic rate (Jones et al, 1972). In addition, it was demonstrated with 51 Cr-albumin studies that excess loss of protein into the GI tract can be noted in 85% of patients.…”
Section: Ménétrier's Disease (Giant Hypertrophy Of the Gastric Rugaementioning
confidence: 96%
“…The condition was first described by Menetrier in 1888 and since then some 200 cases have been reported in the literature. These reports have concerned the pathology (Butz, 1960), the protein turnover (Jarnum and Jensen, 1972;Jones et al, 1972), the gastric protein loss (Citrin, Sterling and Halstead, 1957) and case reports of the various types of presentation, notably acute gastrointestinal (GI) bleeding (Williams, 1956), chronic GI bleeding (Singh, Cumaraswamy and Corrin, 1979), and oedema (Chokas, Connor and Innis, 1959). Diarrhoea has occasionally been reported.…”
Section: Introductionmentioning
confidence: 99%